2020
DOI: 10.1371/journal.pone.0227294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of KRAS, NRAS and BRAF mutations detection in plasma using an automated system for patients with metastatic colorectal cancer

Abstract: BackgroundCell-free DNA detection is becoming a surrogate assay for tumor genotyping. Biological fluids often content a very low amount of cell-free tumor DNA and assays able to detect very low allele frequency mutant with a few quantities of DNA are required. We evaluated the ability of the fully-automated molecular diagnostics platform Idylla for the detection of KRAS, NRAS and BRAF hotspot mutations in plasma from patients with metastatic colorectal cancer (mCRC). Materials and methodsFirst, we evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…All ddPCR positive samples were positive when analyzed using Idylla and thus, there was a strong agreement between the two methods. The analytical sensitivity of Idylla in detecting KRAS mutations has been reported to be in the range of 0.1-1% and that of digital PCR platforms as low as 0.001-0.01% [2,11,13]. In agreement, Vessies et al recently reported that ddPCR is more sensitive when compared with Idylla for detecting KRAS mutations in plasma samples from mCRC patients [14].…”
Section: Discussionmentioning
confidence: 66%
“…All ddPCR positive samples were positive when analyzed using Idylla and thus, there was a strong agreement between the two methods. The analytical sensitivity of Idylla in detecting KRAS mutations has been reported to be in the range of 0.1-1% and that of digital PCR platforms as low as 0.001-0.01% [2,11,13]. In agreement, Vessies et al recently reported that ddPCR is more sensitive when compared with Idylla for detecting KRAS mutations in plasma samples from mCRC patients [14].…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, the test involves many washing and incubation steps with a total analysis time of about 2 h [ 48 ]. Compared to the previously reported biosensors for ctDNA detection in real samples ( Table S3 ) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], the advantages of the proposed multi-plex test are related mostly to the cost, run time, and simplicity, as well as the universality and advanced multiplexing potential.…”
Section: Discussionmentioning
confidence: 98%
“…In the BEAMing procedure, each allele's particular polymerization was assessed on magnetic beads in emulsion PCR through hybridization with wild-type or mutant sequence-targeted fluorigenic probes. Two interesting things about the OncoBEAM RAS CRC technology are that it can give more accurate results for plasma KRAS mutation assaying in patients with mCRC than the Idylla system [ 67 ] and that it can do a wider range of quantitative tests [ 95 ]. In this setting, the OncoBEAM TMRAS CRC plasma test can be incorporated into the early histological report to enable careful prediction of targeted therapy responses and holistic genetic mutational trialing for new histologically authenticated mCRC [ 96 ].…”
Section: Cfdna Detectionmentioning
confidence: 99%
“…(1) Safe-SeqS (2) TEC-Seq Detects somatic mutations in CRC early stages [8], prognosis and prediction to anti-EGFR antibodies or drug selection [8] Not declared Ion Torrent, Illumina, Read Filtering and Trimming, Burrows-Wheeler transform algorithm, Torrent Mapping Alignment Program, SAMtools Genome Analysis Toolkit (GATK), and Picard [128] BRAF mutation analysis Differentiating CRC from precancerous or state and distinctive histologic subtype of CRC [129], correlates with poor prognosis of the disease [130], and predictive biomarker for targeted therapy and prognosis [95] It exists in 5%-10% of CRC tumors and should be used with other markers [131] CBioportal, oncomine [132] APC mutation analysis Exists in 85% of colorectal tumors and 60% of stage I/II CRC patients, differentiating CRC from precancerous or lesions [133],…”
Section: Crc Epigenetic Signaturesmentioning
confidence: 99%